Learning Fractions through Project-Based Learning (PJBL) for Third-Grade Students in Elementary School - Bato Bato; Erni Zulita; Rahmawati Rahmawati; Eni Mintarsih; Giarty Giarty (Universitas Tanjungpura, 2023)
The purpose of the study was to improve the ability of fractions for third grade students in elementary school where students are still experiencing doubts and the way of learning is not right with the right model. Students will be more enthusiastic about learning and able to provide knowledge with what will be received when learning. The method with a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to do it with cycles I and II. Data analysis with CAR based on the results of research conducted during several meetings. The result indicated that in cycle 1, 15 students passed with a percentage of 40% and continued to cycle II with improved planning and implementation using PjBL model. There were 27 students with a percentage of 100% passed in this cycle. The implementation of PjBL model in the learning process can help students to digest the topic.